A Biocompatible and Near‐Infrared Liposome for In Vivo Ultrasound‐Switchable Fluorescence Imaging. Issue 4 (20th January 2020) - Liu, Yang; Yao, Tingfeng; Cai, Wenbin; Yu, Shuai; Hong, Yi; Nguyen, Kytai T.; Yuan, Baohong
Abstract: Fluorescence imaging is a remarkable tool for molecular targeting and multicolor imaging, but it suffers from low resolution in centimeter‐deep tissues. The recently developed ultrasound‐switchable fluorescence (USF) imaging has overcome this challenge and achieved in vivo imaging in a mouse with help from the indocyanine green (ICG) dye encapsulated poly(N‐isopropylacrylamide) (ICG‐PNIPAM) contrast agent. However, the ICG‐PNIPAM has shortcomings, such as concerns about cytotoxicity and blueshifted excitation and emission spectra. This study introduces a newly developed ICG‐encapsulated liposome to broaden the contrast agent selection for USF imaging and resolve the issues mentioned above. The emission peak of the ICG‐liposome is 836 nm with excellent biostability and USF imaging capability. Furthermore, the cell viability test verifies the low cytotoxicity feature. Eventually, both ex vivo and in vivo USF imaging are successfully achieved and 3D USF images are acquired. The ex vivo result confirms that the ICG‐liposome maintains the thermoresponsive characteristic at the right lobe of the liver and is able to conduct the USF imaging. The further in vivo USF imaging demonstrates that although the whole liver emitted fluorescence, only the right lobe of the liver contains the working ICG‐liposome. Abstract : Fluorescence imaging suffers from low resolution in the centimeter‐deep tissues. The indocyanine green encapsulated liposome (ICG‐liposome) is introduced in this study to overcome this issue via the ultrasound switchable fluorescence (USF) imaging. The ICG‐liposome presents an excellent biostability, low cytotoxicity, and outstanding USF imaging capability. 3D USF images are acquired for both ex vivo and in vivo USF imaging.